A gelatin-treated carbon nanofiber/epoxy nanocomposite with significantly improved multifunctional properties. (September 2020) - Zeng, Lijian; Huang, Xianrong; Li, Xueling; Li, Renfu; Li, Yichao; Xiong, Yi
Graphical abstract: Abstract: Good dispersion of carbon nanofillers in a polymer is the prerequisite for the fabrication of advanced multifunctional polymeric nanocomposite. Herein, we report that gelatin, a cost-effective animal protein, is used as a highly efficient bio-surfactant to functionalize carbon nanofibers (CNFs), resulting in nanocomposite with impressively improved mechanical, electrical and processing properties. Excellent dispersion of CNFs in the epoxy resin and good interfacial adhesion between them are realized via gelatin modification, which can be validated from static suspension observation, quantitative macrodispersion analysis and SEM characterization. The electrical percolation threshold of the gelatin-CNFs/epoxy decreases notably from 0.33 wt% to 0.21 wt%. The flexural strength and modulus increase tremendously by 29.1 % and 27.1 % with 0.25 wt% nanofiller addition, which is further proved by nanoindentation test. The wettability of nanocomposite with gelatin treated CNFs is also improved with decreased contact angle. These promising results demonstrate a great potential of the proposed method to be applied in the fabrication of multifunctional polymeric matrix for fiber reinforced plastic composites.